Association between apolipoprotein E ε4 status and the risk of Alzheimer’s disease: a meta-analysis - Zijun Ren; Zhenting Guan; Qingliang Guan; Hongjian Guan; Hongjian Guan (BMC Neuroscience)
Abstract Background The apolipoprotein E ε4 (APOE ε4) status has a controversial role in predicting Alzheimer’s disease (AD) factors. This meta-analysis assessed AD event risk in patients with APOE ε4 status. Materials and methods The relevant English-language articles were identified by searching the Cochrane Library, EMBASE, and PubMed databases. The prognostic significance of APOE ε4 status in AD patients was examined on the basis of pooled hazard ratios (HRs). Results A total of 22 studies published after 1987, including 571,800 patients, were included. Consequently, APOE ε4 status was a risk factor for disease-free survival (DFS, HR = 2.033; 95% confidence interval [CI] = 1.589–2.602; P = 0.000; I 2 = 93.1%) in patients with AD. Additionally, subgroup analysis suggested that the ROC curve was the main risk factor among patients with AD. Conclusions AD patients with different events are managed via different methods; however, the present meta-analysis suggests an increased risk of AD events in patients with different APOE ε4 statuses.